2016
DOI: 10.1021/acs.energyfuels.5b02223
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Based Catalysts for the Hydrotreatment of Fast Pyrolysis Oil

Abstract: Catalytic hydrotreatment is an attractive technology to convert fast pyrolysis oil to stabilized oil products for coprocessing in conventional crude oil refinery units. We report here the use of novel bimetallic NiCu-and NiPd-based (Picula) catalysts characterized by a high Ni content (29−58 wt %) and prepared using a sol−gel method with SiO 2 , La 2 O 3 , kaolin, ZrO 2 , and combinations thereof as the support, for the catalytic hydrotreatment of fast pyrolysis oil. The experiments were performed in a batch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 53 publications
8
47
1
Order By: Relevance
“…Thus, the fresh sample very likely contains highly dispersed NiO species responsible for a broadening of XRD reflections, while particles of larger sizes account for the sharp tops of these peaks. In the 2θ range of 30-40°, a halo is visible, which corresponds to amorphous ZrO 2 , in line with literature data [25]. In situ reduction of the catalyst at 350°C results in the formation of reflections of metallic Ni with a concomitant reduction in the relative intensity of NiO species.…”
Section: X-ray Diffractionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the fresh sample very likely contains highly dispersed NiO species responsible for a broadening of XRD reflections, while particles of larger sizes account for the sharp tops of these peaks. In the 2θ range of 30-40°, a halo is visible, which corresponds to amorphous ZrO 2 , in line with literature data [25]. In situ reduction of the catalyst at 350°C results in the formation of reflections of metallic Ni with a concomitant reduction in the relative intensity of NiO species.…”
Section: X-ray Diffractionsupporting
confidence: 90%
“…The lower reduction peak starting at 250°C (Fig. 1, Ni-Cu/SiO 2 -ZrO 2 ) with a maximum at about 330°C corresponds to reduction of Cu(II) into metallic Cu(0) [25,38] and reduction of a considerable part of the oxidized Ni species [25,39]. A second broad peak extending up to 700°С is associated with hardly reducible nickel silicates.…”
Section: Temperature Programmed Reductionmentioning
confidence: 96%
See 2 more Smart Citations
“…41,[84][85][86] In the conversion of 60 lignocellulosic biomass via pyrolysis, metal lixiviation was identified as one of the causes for catalyst deactivation when Ni nickel and Cucopper were supported over gamma -alumina. 87 De Vlieger et al reported the deactivation of Pt and Pt-Ni supported catalyst in APR of ethylene glycol. The proposed mechanism included the leaching and re-deposition of the alumina phase support, causing a loss of exposed area of the metal active sites.…”
Section: Leaching and Deactivationmentioning
confidence: 99%